CHANGES IN SOME HAEMATOLOGICAL AND BIOCHEMICAL PARAMETERS IN LOCAL BLACK GOATS DURING PREGNANCY - Bamerny, Araz O.; Barwary, Mwafaq S.; Alkass, Jalal E. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present study was aimed to assess and determine the effects of pregnancy on some biochemical and haematological parameters. This experiment was conducted using 16 pregnant of known gestational period and 4 non-pregnant does raised at commercial farm. Results revealed a non-significant differences between pregnant and non-pregnant does for all studied traits. With the advances of pregnancy, it was noticed an increase (P